Divinas tetas: Doing Theology from Mutilated Bodies - André Sidnei Musskopf; Ana Ester Pádua Freire (Religions, 2023)
The article is an exercise in constructing theology from a Latin American perspective in dialogue with queer studies and theologies. The starting point is the tragic death of Lorena Muniz, a transwoman, in the process of getting breast implants making evident aspects of gender oppression, cis-sexist aesthetic pressure, and state neglect of health care specific to the trans population as denounced by ANTRA (National Association of Travestis and Transexuals). From this context, the article discusses a hermeneutics of mutilation in relation to Latin America and to the experience of trans people and introduces countersexuality (Preciado) as a way to resist the mutilations of cis-heteropatriarchy. With those tools in hand, the last part of the article realizes an exercise of theological and religious imagination engaging with the song Vaca profana (Caetano Veloso/Gal Costa) as a possible way of reconciling the reality of Lorena Muniz’ death with the hope for a different future through the symbolism of the divinas tetas [divine tits].